Inmorales, injuriosos y subversivos : las letras durante la Hegemonía Conservadora 1886-1930 (2014)
ABSTRACT:This article analyzes the censorship the letters suffered during the Conservative Hegemony by the government and the Catholic Church, to this effect were studied censored newspapers, Colombian law on press, the Catholic discourse emitted from the Vatican and from the Colombian curia to know what were the points of divergence between these institutions and censored publications.